State Responsibility Model Through Foreign Policy in Handling the Impact of Covid-19 in the Globalization Era - Elyta Elyta; Syarif Redha Fachmi Al Qadrie; Laras Putri Olifiani (Jurnal Politik Indonesia: Indonesian Political Science Review, 2023)
In the era of globalization, the movement of people from one country to another is the cause of the spread of Covid-19. During this global pandemic, the role of the Indonesian Ministry of Foreign Affairs is as an actor who formulates and makes policies. The Covid-19 phenomenon demands the role of the Ministry of Foreign Affairs (Kemenlu) of the Republic of Indonesia (RI) to determine Indonesia's foreign policy in preventing and overcoming the impact of Covid-19. Based on this, research is needed to reconstruct Indonesia's foreign policy model to prevent and overcome the impact of Covid-19 in the era of globalization as the state's responsibility to society. The method used in this research is a qualitative method with a descriptive type of research. This study finds that Indonesia's foreign policy to prevent Covid-19 is to encourage virtual international meetings to unite other countries to resolve the Covid-19 crisis and protect Indonesian citizens (WNI) abroad. The results of the study found that the Indonesian Ministry of Foreign Affairs carried out the reconstruction of Indonesia's foreign policy model to deal with the impact of Covid-19, namely in Indonesian foreign policy.